"In case you hadn't noticed!": Race, Ethnicity, and Women's Wage-Earning in a Depression-Era City - Srigley, Katrina (Labour/Le Travailleur, 2005)
Abstract This article unites an extensive collection of oral histories with the documentary record — newspapers, the census and government records — to examine women’s employment during the Great Depression in Toronto. It asks how privilege and disadvantage based on race/ethnicity, gender and class influenced women’s work experiences. In Toronto’s garment industry and as clerical workers, domestics and teachers the women in this study had various levels of economic stability, came from varied ethnic and racial backgrounds and enjoyed, as a consequence, different job options in a period when employment access was particularly important for women and their families. For instance, despite their shared gender, training and class backgrounds women such as Claire Clarke and Mildred Johnson did not have the same employment options. This article explores the intersection between identity and job access to show why this was so in the 1930s. Ultimately, individual experiences indicate that gender should not be given analytical predominance for understanding all Depression-era labour markets. In some historical contexts and for some women gender had less relevance to their experiences than race, ethnicity, or class.